"If we're not serving our own community, no one else would": The lived experience of providers in ethnically similar therapeutic dyads at South Asian women's organizations. Issue 1 (2nd January 2019) - Reddy, Swathi M.
ABSTRACT: South Asian women's organizations have been established nationwide to meet the unique needs of South Asians impacted by domestic violence. Although services at these community-based agencies are primarily delivered by providers who are South Asian themselves, research into their experiences is sparse and fails to address how sharing facets of their identity affects them and their ability to care for clients. Based on a phenomenological research design, semi-structured interviews were conducted to describe the lived experience of eight South Asian therapists who were currently working at South Asian women's organizations in the New York metropolitan area. Four essential themes emerged from the analysis: (a) disrupting the status quo, (b) navigating psychological distress, (c) examining assumptions of identity, and (d) pushing professional boundaries. The relational complexities of ethnically similar therapeutic dyads revealed deeper issues related to the inseparability of therapy and advocacy, the questioning of cultural norms, the limiting aspects of standard agency procedures, and the straining of professional boundaries.